Guanidinoacetic acid supplementation: A narrative review of its metabolism and effects in swine and poultry - Asiriwardhana, Mahesha; Bertolo, Robert F. (Frontiers in Animal Science, 2022)
Guanidinoacetic acid (GAA) is an amino acid derivative and precursor for creatine which plays a 15 significant role in energy metabolism. However, because of creatine's instability during the 16 manufacturing process and cost, GAA has been explored as an effective alternative to creatine 17 supplements. GAA has been tested as a potential feed additive to enhance energy utilization 18 and growth performance in the poultry and swine industries. Moreover, GAA has been 19 combined with methionine to improve growth outcomes and may also act as an arginine20 sparing agent in birds. The safety of the GAA supplements for animals, consumers, and the 21 environment and its efficacy in numerous livestock species have been proven. This narrative 22 review discusses the scientific evidence regarding the metabolism and effects of GAA 23 supplementation in swine and poultry, identifying the knowledge gaps and future directions for 24 further research on GAA supplementation. A systematic search of the literature identified 25 published research findings related to GAA supplementation in swine and poultry and their 26 findings are summarized in this narrative review to confirm the impacts of GAA 27 supplementation on growth performance, reproductive performance, and meat quality in swine 28 and poultry. Amongst its many demonstrated benefits, GAA is effective at improving body 29 creatine concentration, growth parameters, feed conversion ratio, and performance of animals. 30 Although GAA exerts many non-creatine roles, including the stimulation of insulin secretion, 31 neuromodulation, and vasodilation, further research may require in-depth elaboration.